2017
DOI: 10.1111/jgh.13804
|View full text |Cite
|
Sign up to set email alerts
|

Association between the ulcer status and the risk of delayed bleeding after the endoscopic mucosal resection of colon

Abstract: Cut vessels and severe coagulation injury on post-EMR ulcers, as well as larger polyp size, are risk factors for DPPB. Careful inspection of post-EMR ulcers and prophylactic hemostasis, if necessary, may improve the clinical outcomes of colonoscopic EMR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…A submucosal hematoma is probably caused by a cut-ting and/or coagulation injury of a larger submucosal vessel during p-EMR. Interestingly, a recent Korean study reported that cut vessels and vessels with a severe coagulation injury were associated with post-EMR bleeding for polyps > 5 mm [15]. These novel associations emphasize the importance of inspecting and photodocumenting the post p-EMR resection defect and prompt consideration of technical factors that may minimize the depth of excision, such as greater submucosal lift, use of a smaller snare or use of minimal electrocautery.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A submucosal hematoma is probably caused by a cut-ting and/or coagulation injury of a larger submucosal vessel during p-EMR. Interestingly, a recent Korean study reported that cut vessels and vessels with a severe coagulation injury were associated with post-EMR bleeding for polyps > 5 mm [15]. These novel associations emphasize the importance of inspecting and photodocumenting the post p-EMR resection defect and prompt consideration of technical factors that may minimize the depth of excision, such as greater submucosal lift, use of a smaller snare or use of minimal electrocautery.…”
Section: Discussionmentioning
confidence: 97%
“…Intact visible vessels in the EMR defect do not appear to predict delayed bleeding [14]. However, cut vessels and coagulation injury in the EMR defect may be predictive [15]. Features of the EMR defect indicative of perforation have been described [16], but further work is required to delineate p-EMR defect features that may predict delayed bleeding.…”
mentioning
confidence: 99%
“…Careful inspection and coagulation of exposed nonbleeding visible vessels (with little or no overlying submucosa) in the post-ESD site has been recommended to prevent delayed bleeding in the upper GI tract, 56 but the effectiveness of this method after large colorectal resections is equivocal. 57,58 When using this technique, low-voltage ("soft") coagulation current has been recommended 58 to reduce the risk of perforation and the possibility of pain from postpolypectomy burn syndrome. 57 Given the increased risk of bleeding and/or perforation during and after ESD, endoscopists should be familiar with the different closure devices and techniques available for post-ESD defect closure.…”
Section: Coagulation and Closure After Endoscopic Submucosal Dissectionmentioning
confidence: 99%
“…57,58 When using this technique, low-voltage ("soft") coagulation current has been recommended 58 to reduce the risk of perforation and the possibility of pain from postpolypectomy burn syndrome. 57 Given the increased risk of bleeding and/or perforation during and after ESD, endoscopists should be familiar with the different closure devices and techniques available for post-ESD defect closure. Generally, standard endoclips are successful at closing most perforations that occur during ESD because, typically, these will be small.…”
Section: Coagulation and Closure After Endoscopic Submucosal Dissectionmentioning
confidence: 99%
“…Other studies have reported that the following factors are associated with an increased risk for delayed bleeding: right-sided colon location, use of electrosurgical current not controlled by a microprocessor, intraprocedural bleeding at the time of polyp removal, exposed vessels of the post-EMR ulcer, signs of coagulation injury to the resection bed, and use of anticoagulants. 22,[42][43][44] The intraprocedural bleeding rate in the literature is over 10% in several large series, with delayed bleeding reported in 1.5% to 14% of cases. 45,46 In their large case series of 479 large sessile polyps that underwent EMR, Moss et al 47 reported the following rates of AEs: hospitalization, 7.7%; postprocedural pain, 2.1%; serositis, 1.5%; bleeding (mostly immediate), 2.9%; and perforation, 1.3%.…”
Section: Postprocedural Bleedingmentioning
confidence: 99%